Human rights, globalisation and the Asian economic crisis / Shad Saleem Faruqi - Faruqi, Shad Saleem (Universiti Teknologi MARA Kampus Samarahan, 1999)
Injustice anywhere is a threat to justice everywhere. Human rights abuses in any part of the globe deserve world-wide condemnation because state sovereignty is a shield against external aggression. It cannot be used as a sword against one's own nationals. Haifa century after the adoption of the Universal Declaration of Human Rights, one can say with guarded optimism that freedom is on the march; that the human rights quest has gained a universal appeal. But despite global recognition of the legitimacy of the human rights discourse, there remain disagreement and discord on a number of thorny issues. The essay examines whether the "Asian values" argument is a smokescreen for the perpetuation of authoritarianism or whether it is a genuine attempt to resist the sweep of hegemonic "Western " values. The author warns that the human rights quest is a journey, not a destination and one must remain vigilant against new threats like economic globalisation which has added a new form of oppression to older discriminations.